Light-Mediated Manufacture and Manipulation of Actuators - Han, Dong-Dong; Zhang, Yong-Lai; Ma, Jia-Nan; Liu, Yu-Qing; Han, Bing; Sun, Hong-Bo (Advanced materials (Weinheim), 2016)
Recent years have seen a considerable growth of research interests in developing novel technologies that permit designable manufacture and controllable manipulation of actuators. Among various fabrication and driving strategies, light has emerged as an enabler to reach this end, contributing to the development of actuators. Several accessible light‐mediated manufacturing technologies, such as ultraviolet (UV) lithography and direct laser writing (DLW), are summarized. A series of light‐driven strategies including optical trapping, photochemical actuation, and photothermal actuation for controllable manipulation of actuators is introduced. Current challenges and future perspectives of this field are discussed. To generalize, light holds great promise for the development of actuators. Recent advances in light‐mediated manufacture and manipulation of actuators are highlighted. Several optical fabrication technologies, including UV lithography and direct laser writing, and various photo‐driven strategies, such as optical trapping, and photochemical and photothermal actuation are reviewed. Emerging trends and future perspectives of light‐enabled actuators are discussed.